Sex, lies, and videotape: a content and textual analysis of media coverage of the HIV criminal prosecution of Michael Johnson - Campbell, Chadwick K. (Crime, media, culture, 2022)
Media coverage of HIV criminal cases has deployed sexualized and racialized tropes, and portrayed defendants as villains. Several media analyses of HIV criminal trials have been conducted, though only one was in the US, and none involved young Black gay men, who are disproportionately impacted by HIV. We conducted content and textual analyses of 91 media stories focused on the 2015 case of Michael Johnson, a Black gay college student living with HIV who was convicted under Missouri?s HIV non-disclosure laws. To capture both dominant and resistant meanings in news stories, we included mainstream news outlets, as well as HIV-related, African American and GLBT community-oriented outlets. Open and axial coding were carried out by a team of four researchers and thematic analysis was used to explore how media framed Johnson, his sexual activities, condom use, and alleged nondisclosure. Results showed that media stories portrayed Johnson as dishonest and sexually predatory by drawing on narratives of deception and framing him as the sole agentic actor in his sexual encounters. We argue that these media frames, coupled with what is included and excluded in media coverage negatively impacts public opinion of PLWH, reinforces HIV criminalization ideologies, and performs a disciplinary function in the lives of PLWH.